How Mastery of Linking, Reduction and Assimilation Predicts EFL Learners’ TOEFL Listening Proficiency - Fitriani Fitriani; Akhrif Yahsya (English Education Department at FKIP Nommensen University, 2026)
TOEFL is an international benchmark of academic English proficiency, yet its listening section remains the most demanding because it requires the rapid, real-time processing of natural speech. The difficulty intensifies when connected-speech features—linking, reduction, and assimilation—shift word boundaries and alter pronunciations, posing considerable challenges for test-takers. This study examined how learners’ mastery of these features relates to their listening performance, particularly in TOEFL, using a convergent mixed-method design. Learners completed a TOEFL-like listening test and a connected-speech test developed from a connected-speech analysis of the listening materials. Results indicated that connected-speech skills significantly predicted listening comprehension, with linking generally easier to process, while reduction and assimilation frequently caused misperceptions. These findings highlight that limited mastery of connected speech directly affects listening performance and underscore the need for targeted, feature-specific instruction. Pedagogically, to enhance listening instruction—especially in TOEFL preparation training—the curriculum should integrate intensive practice with authentic materials that train students to comprehend and produce connected speech, thereby improving their listening performance and maximizing their TOEFL listening outcome.